Alström’s Syndrome, Leber’s Hereditary Optic Neuropathy, or Retinitis Pigmentosa? A Case of Misdiagnosis - Palaiologos Alexopoulos; Chrysanthos Symeonidis; Tryfon Rotsos (Case Reports in Ophthalmological Medicine)
A case of a patient with the Alström syndrome (AS) that was misdiagnosed as Leber’s hereditary optic neuropathy or retinitis pigmentosa for 13 years is presented. AS is a rare genetic disorder caused by mutations in the ALMS1 gene. AS may lead to abnormal ciliary formation and function. AS affects metabolism, and symptomatology includes type 2 diabetes mellitus (T2DM), obesity, hypogonadism and gynecomastia in males, progressive bilateral sensorineural hearing loss, cardiomyopathy, nonalcoholic fatty liver disease (NAFLD), cirrhosis, and chronic progressive kidney disease. The onset of the above symptoms may vary significantly. The ophthalmic manifestation is early onset cone-rod dystrophy that starts as progressive vision loss, photophobia, and nystagmus in the first months of life. An accurate diagnosis may enable specialists to facilitate a significantly positive effect in the everyday life of a patient. Genetic counseling may also be recommended for these patients. Diagnosis was confirmed by DNA testing, thus highlighting its necessity in everyday practice.